Neogene monogenetic volcanism from the Northern Puna region: products and eruptive styles - Maro, Guadalupe (2017)
The Neogene mafic volcanism of the Northern Puna region in the Central Andes isrepresented by scoria cones and lava flows dispersed over a wide region (c. 9150 km2) as isolated or poorly clustered centres. Although all the products are basaltic andesites to andesites, the behaviour of these magmatic systems resembles that seen in basaltic monogenetic fields. These centreswere studied with the aim of defining the main volcanic lithofacies and evaluating the eruptive styles. The results suggest that the eruptions developed under a dry strombolian dynamic, with brief periods of lava fountaining and hydrovolcanism, the latter usually restricted to the early stagesof cone construction. Changes in eruptive style are thought to be caused by variations in both the internal (e.g. magma ascent) and external (e.g. surficial water availability) conditions. The transitions do not reflect compositional changes, as evidenced by the small chemical differences observed among the products of the studied eruptive centres. Stratigraphic analysis, in additionto a few pre-existing radiometric dates, suggests that this volcanic activity occurred during the Late Miocene to Early Pliocene. This information supports the inference that these eruptions occurred before the peak of Southern Puna mafic volcanism and that they were coeval with eruptions of some of the most important silicic calderas of the Altiplano-Puna Volcanic Complex. Thegood preservation of volcanic edifices reveals that erosion rates were extremely low, in agreement with the high aridity conditions that have prevailed in the Puna region since the Mid- to Late Miocene.